Women in Nuclear Science & Technology in India: Challenges & Opportunities - Arpita Datta; Dr. Alpana Goel; Ashok Kumar Jain (International Journal of Nuclear Security, 2022)
Women have been actively contributing toward frontline research and development of various advanced technologies in the nuclear domain and playing a crucial role in key positions. However, proportional representation of women in various decision-making positions at higher levels in politics, diplomacy, military affairs, science, and technology remains low, and most of these positions remain male-dominated. We see that women often find it difficult to achieve leadership roles for several reasons, but often from an implicit bias in society. The stereotypical image of women in society is still propagated very discreetly. In recent times, Indian women have made big strides in several frontline sectors like Information Technology (IT), Biotechnology, and on corporate levels. More recently, organizations, including the Indian government, have been promoting an awareness of gender equality in various fields including nuclear technology. Amity University has also been motivating women academicians to take a lead in various fields including nuclear technology and nuclear security. This paper describes various initiatives that the Government of India has taken, along with many Indian organizations, including Amity University, to promote women in various fields especially in nuclear technology. This paper also discusses the opportunities for Indian women, their contributions, and challenges.
Keywords: Nuclear Science; Nuclear security; Indian women; challenges; opportunities